Analysis of the impact of local discretization in the area of technological cutouts on stress concentrators - Alexandru George Gheorghe; Anișoara - Gabriela Cristea (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding)
This study aims to analyze and compare the influence of steel flat bar beveling around technological cutouts on the stress state of a chemical tanker with a deadweight of 35,622 tons (TDW). Technological cutouts, which are essential for the installation of equipment, passage of cables, and other functional purposes, can cause stress concentration in the ship's structure, increasing the risk of cracking and localized failure. To assess the impact of beveling, two structural models are compared: one with steel plate beveling and one without. Using finite element analysis (FEM) through FEMAP/NX Nastran software, stresses and displacements around the cutouts are examined at four representative points along the cutout’s circumference. The results reveal significant differences in stress distribution between the two models, demonstrating the effectiveness of beveling in reducing local stress concentrations. This study provides insights into improving structural integrity and safety in ship design by addressing the risks associated with technological cutouts.